PERAN YAYASAN DALAM PENGELOLAAN BIDANG PENDIDIKAN PADA PERGURUAN TINGGI SWASTA - Suryarama, Suryarama (Jurnal Organisasi dan Manajemen, 2009)
From the five foundations, four of them (80%) the foundation board have a contribution in managing private university especially in financial field. Main problems appear between the persons of the foundation board and those who manage private university are caused by the administration management problem (40%), financial problem (20%), and other problems (40%). The people above have commitmenst to overcome the problems beside attending a board meeting to solve their problems. The authority of the board is not balance if compared with the private university manager for 80% of the private university managers have a contribution and take a part in managing the administration and financial field.